A FACTOR ANALYTICAL STUDY ON THE ANTECEDENTS OF SELF-ESTEEM - IMMANUEL THOMAS & H. SAM SANANDA RAJ (Psychological Studies 1985, Vol. 30, No. 2, 1985)
A factorial study on the antecedent variables of self-esteem was conducted on a stratified sample of 624 secondary school pupils (314 boys and 310 girls) of Kerala state. The variables used for the study were: socioeconomic status, parental attitude, home environment, home relations, acceptance-rejection, dependence-independence, autocracy-democracy, mutual trust and approval, and self-esteem. The data were analyzed using Pearson r, followed by factor analysis. The results of factor analysis of the 9 X 9 correlation matrix revealed three significant factors, viz., 'Family Harmony', 'Physical Facility', and 'Parenting Practices'. Self-esteem loaded significantly on all the three factors